Proses Pembelajaran Biologi Pada Masa Pandemi Covid-19 di Universitas Qamarul Huda Badaruddin - Hidayah, Thauhidayatul (LPPM Universitas Qamarul Huda Badaruddin, 2020)
Online learning is one of the learning methods applied during the COVID-19 pandemic. The Biology study program of the University of Qamarul Huda Badaruddin has carried out online learning since the Even Semester of the 2019/2020 Academic Year to the Odd Semester of the 2020/2021 Academic Year. This study aims to analyze the learning process in the Biology department during the COVID-19 pandemic. This research is a qualitative descriptive study, data collection was carried out by interviews and Google form containing 11 questions to students of the 2018 and 2020 batches. The results of this study indicate that the online lecture process at the Biology Study Program at the University of Qamarul Huda Badaruddin is running well (smoothly), it is shown through learning / lectures that take place according to a predetermined schedule (66.7%), enthusiasm during learning is very high (83.33%), communication with lecturers (66.66%) and understanding of the material is quite good (58.33 %). The obstacles during the online learning process include students who are still rigid with the online method (class of 2020), dissatisfaction (in practicum), difficulty in connecting (weak network) from the area where they live, and requiring relatively large internet quota. The conclusion of this study is that the online learning process in the Biology study program at the University of Qamarul Huda Badaruddin went well during the COVID-19 pandemic, but further evaluation needs to be done for the next online learning.